FACTORS ASSOCIATED WITH OVERWEIGHT/OBESITY AMONG ADULTS IN URBAN INDONESIA - Helda Khusun; Luh Ade Ari Wiradnyani; Nora Siagian (Persagi, 2015)
Overweight/obesity is increasing in developing countries, including Indonesia, being more prevalent in urban than rural areas. Understanding about associated factors of overweight/obesity is important for intervention purposes. The study objective was to assess factors associated with overweight/obesity in urban Indonesians. This cross-sectional study involved primary data collection among 864 adults aged 18-45 years in five major urban cities of Indonesia. Weight, height, waist and hip circumference were measured, and overweight/obesity was defined as BMI>25 kg/m2. Factors associated to overweight/obesity was ellicited by logistic regression. The study showed that proportion of overweight/obesity was significantly higher among women than men (42.8% and 29.2%). Median total energy intake was 1974 kcal/day, and median fat intake was high (75.3 g; 25th-75th percentile: 49.6-109.4 g). More than 70 percent of subjects consumed high energy dense food/beverages often. Only around 27 percent of the subjects had high intensity physical activity/PA level and more than 50 percent spent >6 hours using TV/computer, indicating low PA level. After adjusting for confounders, often consumption of high energy dense food consistenly showed association, although not signficant, with overweight/obesity. Moreover, men with higher sedentary activities indicated by TV/computer usage >6 hours/day and women with less days of performing vigorous PA had 1.4 and 3 times higher odds to become overweight/obese, respectively. Thus, overweight/obesity prevention should focus on reduction of consumption of high-dense energy food, including fat intake; coupled with increasing PA level by having more days of vigourous recreational PA and reduction of TV/computer usage, especially among married older urban adult.